Kebijakan Pengembangan Bimbingan Perkawinan Pra Nikah Berbasis Hybrid Learning - Hartawan, Lalu Kiagus (JURNAL ILMIAH GEMA PERENCANA, 2024)
This article reviews premarital marriage guidance for prospective brides and grooms as one of the government's priority programs that provide knowledge and skills for married couples to build harmonious and prosperous households that do not run effectively and efficiently between the output and outcome produced and those intended to be achieved in the implementation of premarital marriage guidance at the Ministry of Religion of West Nusa Tenggara Province based on hybrid learning, due to factors such as the quality of human resources, premarital marriage guidance materials, and limited access to technological devices and the internet. In this regard, in analyzing this problem, the author uses a qualitative approach method. The results of the analysis are: First, the quality of guidance requires a different approach, because the literacy skills of the participants in the guidance vary, and most still have difficulty understanding and following the marriage guidance material provided. Second, the level of public trust, especially in traditional communities that still believe in local wisdom patrons, who find it difficult to apply knowledge according to the marriage guidance material they obtain into their married lives. Third, not all prospective couples have adequate access to technological devices and the internet to follow the hybrid learning method, especially in remote areas or with limited digital infrastructure. The conclusion is that pre-marital marriage guidance for prospective brides and grooms needs to be developed to minimize the occurrence of divorce and build a harmonious family.